A Cell-Based Screening Platform Identifies Novel Mosquitocidal Toxins - O’Neal, Melissa A. (2013)
Pesticides currently in widespread use often lack species specificity and also become less effective as resistance emerges. Consequently, there is a pressing need to develop novel agents that are narrowly targeted and safe to humans. A cell-based screening platform was designed to discover compounds that are lethal to mosquito (Anopheles and Aedes) cells but show little or no activity against other insect (Drosophila) or human cell lines. Mosquito-specific, aqueous-stable cytotoxins were recovered at rare frequencies. Three of these were profiled for structure-activity relationships and also assessed in whole-animal toxicity assays. In at least one test case, species-specific cytotoxicity seen in culture effectively translated to the whole-animal level, with potent toxicity against Anopheles yet none against Drosophila. Therefore, this initiative has the potential to advance novel mosquitocidal agents and, in a broader sense, could establish a versatile platform for developing customized pesticides that selectively target other disease vectors as well.